PEMBUDIDAYAAN JAMUR KUPING PADA KAYU TURI (Sesbania grandiflora (L.) Poir.) - Sihati Suprapti (Jurnal Penelitian Hasil Hutan, 1988)
Ear  mushroom (Auricularia polytrica)  was  cultivated on turi  logs.   The  logs  were  kept  slanted  on an  angle  of ± 60°  with  bamboo  supports   before  being inoculated  with spawn of ear mushroom  at Bogor.  The mature  mushroom were harvested  daily  after  the  growth   of  the  fruiting   body.The  logs start  producing   mushroom   two  months  after  inoculation.  After  seven  month   of  observation, the  average total yield  per  log was 0.589 kg  (at the  base of  trunk),  0.885 kg (middle  of trunk), 0.648  kg (top  of trunk)  and 0.141  kg (branch).The  total  yield  during seven  month   observation   was obtained  from  the  base of  trunk  (61.864 kg), middle  of  trunk (179.120  kg),  top of trunk  (203.656 kg) and branch (74.778 kg) per m3 of log.